La narración en la enseñanza de la ética - Zabala Hernández, Mauricio (2024)
This paper seeks to call into question the usual way in which ethics is taught and to support the use of narrations as an important pedagogical tool within moral education. Since ethics has less to do with the acquisition of knowledge than with a disposition for action, it could very well use narrative formats to develop the sensibility necessary to build reflexive, critical and empathic citizens. After all, the anthropological nature of human beings is already narrative, and every form of good life implies ultimately the possibility of it being told. The practice of narrating amounts to a defense of the search for and the construction of meaning inside a society where rapidity and fragmentary information seem to determine the only possibility of self-constitution.